Implementasi Demokrasi dan Legitimasi Penjabat Kepala Daerah di Indonesia - Abustan Abustan (Universitas Muhammadiyah Malang, 2022)
Indonesia is a country based on the rule of law. As a country, the Indonesian state is also an organization of power with a democratic concept that includes an understanding of the fields of politics and government. However, as a legal state, state power must have legitimacy or be regulated by law (constitutional) so that the state government's power is limited by law. The dynamics of local government have recently received a lot of public scrutiny, especially the controversy over the appointment of acting regional heads. Lately, of course, this is not limited to the essence of democracy with the rule of law. This study takes the subject of the implementation of democracy which contains legal truth and provides justice (legal justice). The research aims to find out the aspects that are of public concern in the appointment of acting regional heads. This research is empirical research that uses a sociological juridical approach. The reality of conditions that exist in the regions, in the research conducted found various questions from the community, why the appointment of acting regional heads is only through the appointment of the central government. That is the development of the dynamics of democracy found in the research conducted.